Penerapan Metode Belajar Sambil Bermain Guna Memenuhi Kebutuhan Pengembangan Diri Anak - Fajar Utama Ritonga; Helga Dilena (Yayasan Literasi Sains Indonesia, 2022)
To increase a child's knowledge, education must be taught from an early age. Learning is defined as all activities carried out by each individual so that their behavior is different after the learning process. By playing, children express themselves without being forced with feelings of pleasure. Playing can provide many benefits to their development and channel their energy also discover new things. Both learning and playing are things that naturally all children should be able to experience. Every child would be happier if they could learn activities while playing. Learning while playing expects them to be able to create results for good development. To achieve the personal development needs of children at the LSM KOPA Jl. Syah Bandar No.23, A U R, Medan Maimun, Medan, Sumatera Utara, learning while playing activities are carried out which aims to help children achieve the goal of being able to learn and also play at the same time. It is also expected to be able to educate how important it is to fulfill learning and play activities for children's personal development needs.